ANALISIS TEKANAN PEMBAKARAN PADA MESIN DIESEL MENGGUNAKAN METODE PRESSURE COMBUSTION ANALYSIS - Moch. Syaiful Anwar; Mochamad Shaleh (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2024)
His study aims to analyze combustion pressure characteristics in a diesel engine using the Pressure Combustion Analysis (PCA) method. The research employed a quantitative descriptive approach through direct measurement of combustion pressure in each cylinder of a Sulzer 12 ZV 40/48 diesel engine under constant operating load conditions. The analyzed parameters included peak combustion pressure, combustion pressure balance, ignition delay, pressure at crank angle 340°, and indications of abnormal combustion. Data acquisition was conducted using Haliza Machinery & Diesel Engine Analyzer and processed using SoftHaliza software. The results showed that the average combustion pressure reached 59.33 bar with pressure deviations among cylinders remaining below the allowable limit, indicating that the overall combustion condition was still within normal operating standards. Comparative analysis before and after the application of fuel additive demonstrated an increase in average combustion pressure from 57.91 bar to 59.33 bar, indicating improved combustion performance and smoother combustion characteristics. However, several cylinders still exhibited indications of incomplete combustion and combustion pressure imbalance caused by variations in fuel injection and combustion quality. In addition, the PCA method proved effective for early detection of ignition delay, combustion abnormalities, and potential cylinder performance degradation. Therefore, Pressure Combustion Analysis can be applied as an effective predictive maintenance method to improve diesel engine reliability and operational efficiency.